2007
DOI: 10.1155/2007/350279
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of dexmedetomidine and midazolam used for sedation of patients during upper endoscopy: A prospective, randomized study

Abstract: The aim of the present prospective, randomized study was to investigate and compare the safety and efficacy of dexmedetomidine versus midazolam in providing sedation for gastroscopy. A total of 50 adult patients (25 patients receiving dexmedetomidine and 25 patients receiving midazolam), 18 to 60 years of age, and rated I and II on the American Society of Anesthesiologists physical status classification system were included. A brief questionnaire was used to collect demographic data; patients were asked to rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
117
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(126 citation statements)
references
References 21 publications
5
117
1
3
Order By: Relevance
“…Retching was found to be significantly lower and endoscopists satisfaction was higher. Decreasing of retching reflex may be due to its sympatholytic and vagomimetic effects of dexmedetomidine .The findings of our study were similar to the study of Yavuz Demiraran,Esin Korkut and et al (2005)(2006) 4 who did a prospective randomised study to compare efficacy of dexmedetomidine versus midazolam used for sedation during upper endoscopy .Hemodynamic parameters were similar in both groups High satisfaction levels were seen in both groups The anxiety score after the procedure was lower in patients receiving dexmedetomidine than those receiving midazolam Endoscopist satisfaction on sedation of patients was significantly higher in the patients receiving dexmedetomidine than those receiving midazolam Hence it was concluded that ,Dexmedetomidine being safe and effective, seems to be a good alternative to midazolam for sedation of patients during upper endoscopy. In our study 5 cases experienced gagging and hiccup,10 cases has increased salivation which was managed by suctioning and positioning the patient in lateral position .No other active intervention was required One case had vomiting., during the procedure and required additional dose of ketamine.…”
Section: Ramsay Sedation Scoresupporting
confidence: 92%
“…Retching was found to be significantly lower and endoscopists satisfaction was higher. Decreasing of retching reflex may be due to its sympatholytic and vagomimetic effects of dexmedetomidine .The findings of our study were similar to the study of Yavuz Demiraran,Esin Korkut and et al (2005)(2006) 4 who did a prospective randomised study to compare efficacy of dexmedetomidine versus midazolam used for sedation during upper endoscopy .Hemodynamic parameters were similar in both groups High satisfaction levels were seen in both groups The anxiety score after the procedure was lower in patients receiving dexmedetomidine than those receiving midazolam Endoscopist satisfaction on sedation of patients was significantly higher in the patients receiving dexmedetomidine than those receiving midazolam Hence it was concluded that ,Dexmedetomidine being safe and effective, seems to be a good alternative to midazolam for sedation of patients during upper endoscopy. In our study 5 cases experienced gagging and hiccup,10 cases has increased salivation which was managed by suctioning and positioning the patient in lateral position .No other active intervention was required One case had vomiting., during the procedure and required additional dose of ketamine.…”
Section: Ramsay Sedation Scoresupporting
confidence: 92%
“…14,15 Other studies have also reported better satisfaction scores with dexmedetomidine. 9,11,16,17 However, Zeyneloglu et al have reported better satisfaction scores with midazolam-fentanyl combination as compared to dexmedetomidine in extracorporeal shock wave lithotripsy (ESWL) when used alone. 18 The authors also concluded that probably it was not effective as a sole agent in ESWL.…”
Section: Resultsmentioning
confidence: 99%
“…It is advisable that the protective reflexes are not suppressed and that the surgeon can work comfortably. Therefore, a sufficient dose of a conscious sedation medication should be administered, and monitoring methods should be performed [11]. In our study, we ensured that the patients in each group were motionless but sufficiently conscious to cooperate.…”
Section: Discussionmentioning
confidence: 99%